Women's contributions to agricultural production and food security: current status and perspectives in Syria - Kaisi A.; Al Zoughbi S. (Mainstreaming gender dimensions in water management for food security and food safety, 2007)
Syria is among the low-income food-deficit countries. Despite progress in agriculture, current production cannot keep up with population growth that is considered one of the highest rates in the world. This paper presents a preliminary assessment of food security issues in Syria through the most recent relevant studies conducted at global, regional and Syrian national levels. The assessment covers Syrian governmental plans and policies towards achieving food security and fighting hunger in the rural areas as well as the ongoing research of FAO, UNDP, WHO, UNICEF and other international organizations. The first part of the paper is a definitional and conceptual framework. The second one is an analysis of recent literature review (at global, national and household levels) with special reference to the linkages between food security and the sustainable livelihood approach. While the last part summarizes the state of food security in Syria and concludes discussing some research needs. It was shown that families not having enough food accession and availability. Moreover, challenges can be met through increasing awareness-raising campaigns on the use of balanced and sanitary food, reducing thinness rates and malnutrition among children.
2. Regional Coordination Workshop of GEWAMED (Mainstreaming Gender Dimensions into Water Resources Development and Management in the Mediterranean Region), 2007/03/12-14, Larnaca (Cyprus)